PENGARUH SOCIAL COMMERCE TERHADAP PENJUALAN PRODUK KECANTIKAN DI KALANGAN GENERASI Z : STUDI KASUS PENJUALAN DI TIKTOK SHOP - Abni, Nurshahira (Jurnal Tata Rias, 2025)
Abstract This study aims to analyze the influence of social commerce, particularly TikTok Shop, on the purchasing behavior of beauty products among Generation Z. Utilizing a quantitative approach, data were collected through questionnaires distributed to students at Universitas Negeri Padang. The findings reveal that 72.74% of respondents perceive a high interest from Generation Z in using TikTok Shop, while 69.2% express satisfaction with purchasing cosmetic products through the platform. These results indicate that TikTok Shop effectively influences Generation Z's purchasing decisions, especially through interactive features such as live shopping, user reviews, and influencer endorsements. The implications of this study underscore the importance of marketing strategies that leverage social commerce to engage digitally active young consumers.